Asset structure and Profitability Nexus – Evidence from Commercial Banks in Nigeria (2019)
This paper investigated the Impact of Capital Structure on Profitability of Commercial Banks in Nigeria, between 2005 and 2014. The study carried out Static Analysis of the Nexus between Capital Structure and Profitability of Commercial Banks in Nigeria, with focus on 10 selected Commercial Banks in Nigeria. The techniques of Pooled OLS Estimation, Fixed Effect Estimation (FEE) and Random Effect Estimation (REE) were employed in an attempt to arrive at the most consistent and efficient static estimation of the Panel Mode. The proxies of Debt Finance (DF), Equity Finance (EF) and Debt Equity Ratio (DER) for Capital Structure while Profit after Tax (PAT) is used as a measure of Bank Profitability. The result of the study showed that Debt Finance exert positive but insignificant influence on Commercial Bank’s Profitability, while the ratio of Debt-Equity influence on Commercial Banks’ Profitability was found to be negative for the period investigated. The study therefore recommend that Commercial Banks should be more levered as this significantly influence the level of Profitability, however they should adopt the right finance mix that is not extremely lopsided to obtain the right balance between Business and Financial Risk.